Solid polymer electrolytes: Ion conduction mechanisms and enhancement strategies - Dongmei Zhang; Xianglong Meng; Wenyan Hou; Weihao Hu; Jinshan Mo; Tianrong Yang; Wendi Zhang; Qianxiao Fan; Lehao Liu; Bing Jiang; Lihua Chu; Meicheng Li (Nano Research Energy, 2023)
Solid polymer electrolytes (SPEs) possess comprehensive advantages such as high flexibility, low interfacial resistance with the electrodes, excellent film-forming ability, and low price, however, their applications in solid-state batteries are mainly hindered by the insufficient ionic conductivity especially below the melting temperatures, etc. To improve the ion conduction capability and other properties, a variety of modification strategies have been exploited. In this review article, we scrutinize the structure characteristics and the ion transfer behaviors of the SPEs (and their composites) and then disclose the ion conduction mechanisms. The ion transport involves the ion hopping and the polymer segmental motion, and the improvement in the ionic conductivity is mainly attributed to the increase of the concentration and mobility of the charge carriers and the construction of fast-ion pathways. Furthermore, the recent advances on the modification strategies of the SPEs to enhance the ion conduction from copolymer structure design to lithium salt exploitation, additive engineering, and electrolyte micromorphology adjustion are summarized. This article intends to give a comprehensive, systemic, and profound understanding of the ion conduction and enhancement mechanisms of the SPEs for their viable applications in solid-state batteries with high safety and energy density.